Beyond COVID-19 Lockdowns: Rethinking Mathematics Education from a Student Perspective - Almarashdi, Hanan Shaher (Emerging Science Journal, 2024)
The COVID-19 pandemic has recently reshaped education and life around the world. Undoubtedly, the return to face-to-face learning has been affected after two years of distance learning. However, research that focuses on post-COVID-19 is still limited. Therefore, this study investigates how students perceive the experience of returning to face-to-face learning after distance learning within the context of the United Arab Emirates (UAE). It emphasizes the possibilities and challenges that could be faced in improving face-to-face mathematics education. This study applied an exploratory sequential mixed-method approach, which involved collecting qualitative data from 13 students through a focus group, and then quantitative data was collected from 243 Cycle 2 and 3 students. The qualitative data were coded and analyzed thematically, while descriptive analysis was used to analyze the quantitative data. The qualitative and quantitative results revealed consensus on the main challenges that students experience as they return to face-to-face learning. On top of these challenges are students' lack of study skills, excessive use of technology, and high levels of math test anxiety. Research findings showed students’ preference for face-to-face learning while adding some aspects of distance learning. The results of this study are also expected to be a reference in the development of a new sustainable paradigm of face-to-face learning and as study material for subsequent research related to rethinking math education after COVID-19. Doi: 10.28991/ESJ-2024-SIED1-010 Full Text: PDF